Salvaging the 2013 Federal Law Clerk Hiring Season - Carl Tobias (Washington University Law Review, 2013)
Ten years ago, the judiciary instituted the Federal Law Clerk Hiring Plan, an employment system meant to regularize hiring in which most circuit and district court jurists voluntarily participated. Throughout the succeeding decade, this process operated effectively for innumerable trial judges, but functioned less well for appellate jurists. In early 2013, the U.S. Court of Appeals for the District of Columbia Circuit revealed that all its members "will hire law clerks at such times as each individual judge determines to be appropriate," concomitantly explaining "the plan is [apparently] no longer working." With these statements, the D.C. Circuit explicitly acknowledged what had been the reality for the last decade regarding much court of appeals employment. However, the notice sparked a critical hiring frenzy among district jurists. Because that phenomenon of early district court hires may eviscerate the 2003 Hiring Plan, which substantially reduced the complications that had acutely infected the process since the 1980s, this problematic development merits review. I initially detail the clerk hiring process’ relatively checkered history, ascertaining previous endeavors to improve the clerkship scheme lacked efficacy, although the practices formulated in 2003 were successful. The piece next scrutinizes the present season, detecting that certain actions by jurists closely resemble troubling elements of measures in place before. Finding the plan’s imminent collapse essentially imposes disadvantages on law students that eclipse its benefits and finding no alternative regimen preferable, I suggest that districts and members remain committed to the procedures that have served applicants, legal education, courts and jurists well for ten years.
Keywords: clerkship; clerk; judge; hiring; hire; Federal Law Clerk Hiring Plan; employment